Coming to Terms with Democracy : Federalist Intellectuals and the Shaping of an American Culture, 1800-1828 - Foletta, Marshall, 1955- (Book collections on Project MUSE., 2001)
"In Coming to Terms with Democracy, Marshall Foletta contends that by callling for a new American literature in their journal, the second-generation Federalists helped American readers break free from imported neoclassical standards, thus paving the way for the American Renaissance."--BOOK JACKET.